Analysis of the use of information technology and digital banking on e-satisfaction with e-trust as a moderating variable - Arfi Tsani Hasnan Rifqi; Agustini Tanjung (Enrichment : Journal of Management, 2023)
The purpose of this research is to find out how the use of information technology and digital banking affects e-satisfaction through e-trust at PT. Bank Central Asia in Cikarang. This type of research is quantitative. Data analysis used was descriptive and inferential statistical analysis with the help of SmartPLS version 3 software. Data collection was carried out through questionnaires to 170 respondents from PT. Bank Central Asia, Tbk (BCA) in Cikarang, Bekasi Regency. Based on all the tests that have been carried out, it shows that information technology has a weak effect of 0.128 or (12.8%) and is not significant on electronic satisfaction with P-Value (0.135 > 0.05), digital banking has a weak effect of 0.267 or (26.7%) but is significant on electronic satisfaction (Y) with P-Value (0.029 < 0.05), information technology moderated by electronic trust produces a negative value of (-0.149%) or (-14.9%) and is not significant with the P-Value (0.183 > 0.05 ) on electronic satisfaction and it can be explained that electronic trust does not moderate the influence relationship between information technology on electronic satisfaction (Y) P-Value (0.183 > 0.05). The last result is that digital banking is moderated by electronic trust that has an effect (0.132%) or 13.2% on electronic satisfaction and also cannot moderate the influence relationship between digital banking on electronic satisfaction with a P-Value (0.229 > 0.05), but electronic trust (Z ) care moderately (52.9%) partially to electronic satisfaction.